Comparison of hepatic arterial infusion chemotherapy with mFOLFOX vs. first-line systemic chemotherapy in patients with unresectable intrahepatic cholangiocarcinoma - Yang, Zhenyun; Fu, Yizhen; Wu, Weijie; Hu, Zili; Pan, Yangxun; Wang, Juncheng; Chen, Jinbin; Hu, Dandan; Zhou, Zhongguo; Chen, Minshan; Zhang, Yaojun (Frontiers in Pharmacology, 2023)
Background: Systemic chemotherapy (SC) remains the only first-line treatment for unresectable intrahepatic cholangiocarcinoma (iCCA). Hepatic arterial infusion chemotherapy (HAIC) has been recently proven to be effective in managing hepatocellular carcinoma (HCC). Hence, our study aims to investigate the safety and efficacy of HAIC in treating unresectable iCCA patients.We reviewed 146 patients with unresectable iCCA who had received HAIC or SC between March 2016 and March 2022 in a retrospective manner. Outcomes of patients and safety were compared between the HAIC and SC group.Results: There were 75 patients and 71 patients in the HAIC group and SC group, respectively. A total of 75 and 71 patients were enrolled into the HAIC group and SC group, respectively. The median OS in the HAIC group and SC group was 18.0 and 17.8 months (P=0.84), respectively. The median PFS in the HAIC group and SC group was 10.8 and 11.4 months (P=0.59), respectively. However, HAIC group had significantly longer intra-hepatic progression-free survival (IPFS) than SC group (P=0.035). The median IPFS in the HAIC group and SC group was 13.7 and 11.4 months, respectively. According to the OS (P=0.047) and PFS (P=0.009), singletumor patients in HAIC group appeared to benefit more. In addition, the overall 3 incidence of adverse events (AEs) was lower in the HAIC group than SC group.Our study revealed that HAIC was a safe and effective therapeutic regimen for unresectable iCCA with better intrahepatic tumor control when compared to SC. Meanwhile, patients with single tumor were the most likely to benefit from HAIC than SC.